2005
DOI: 10.1086/444472
|View full text |Cite
|
Sign up to set email alerts
|

A High-Density SNP Genomewide Linkage Scan for Chronic Lymphocytic Leukemia–Susceptibility Loci

Abstract: Chronic lymphocytic leukemia (CLL) and other B-cell lymphoproliferative disorders (LPDs) show clear evidence of familial aggregation, but the inherited basis is largely unknown. To identify a susceptibility gene for CLL, we conducted a genomewide linkage analysis of 115 pedigrees, using a high-density single-nucleotide polymorphism (SNP) array containing 11,560 markers. Multipoint linkage analyses were undertaken using both nonparametric (model-free) and parametric (model-based) methods. Our results confirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 32 publications
(38 reference statements)
1
58
0
Order By: Relevance
“…65 We observed 18 chromosomal regions attaining an NPL score X2.0 when LD was ignored, and 16 of these regions resulted in NPL scores X2.0 when LD was considered. We found that our methodology for eliminating high-LD SNPs was consistent and actually more conservative than that used by Sellick et al, 64 who also used a 10K SNP panel for study of a complex disease. We observed a median intermarker distance of 0.344 Mb (25th and 75th percentile 0.156-0.709 Mb) after elimination of high-LD SNPs, and Sellick et al 64 observed a median intermarker distance of 0.17 Mb (25th-75th percentile 0.06-0.38) after removal of high-LD SNPs by selecting a single SNP from clusters of SNPs with an r 2 > 0.4.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…65 We observed 18 chromosomal regions attaining an NPL score X2.0 when LD was ignored, and 16 of these regions resulted in NPL scores X2.0 when LD was considered. We found that our methodology for eliminating high-LD SNPs was consistent and actually more conservative than that used by Sellick et al, 64 who also used a 10K SNP panel for study of a complex disease. We observed a median intermarker distance of 0.344 Mb (25th and 75th percentile 0.156-0.709 Mb) after elimination of high-LD SNPs, and Sellick et al 64 observed a median intermarker distance of 0.17 Mb (25th-75th percentile 0.06-0.38) after removal of high-LD SNPs by selecting a single SNP from clusters of SNPs with an r 2 > 0.4.…”
Section: Discussionmentioning
confidence: 54%
“…We found that our methodology for eliminating high-LD SNPs was consistent and actually more conservative than that used by Sellick et al, 64 who also used a 10K SNP panel for study of a complex disease. We observed a median intermarker distance of 0.344 Mb (25th and 75th percentile 0.156-0.709 Mb) after elimination of high-LD SNPs, and Sellick et al 64 observed a median intermarker distance of 0.17 Mb (25th-75th percentile 0.06-0.38) after removal of high-LD SNPs by selecting a single SNP from clusters of SNPs with an r 2 > 0.4. It is possible that LD may still have influenced our results, and it is also possible that we may have missed other potentially interesting regions by not assessing LD on the complete genome.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Intriguingly, a recent SNP linkage analysis of familial chronic lymphocytic leukemia (CLL) provides evidence for linkage at 11p12, overlapping with the linkage peak reported here for RA. 54 Perhaps this indicates the involvement of common B cell genes in these disorders. Notably, CLL is often accompanied by the presence of autoantibodies, and current views of B-CLL pathogenesis invoke B cell autoreactivity as contributing to tumor development.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of lymphomas, a family history of any hematopoietic malignancy was found to be associated with 2-3 fold increased risk of NHL [6,7]. Genome-wide linkage scans of CLL families revealed a number of chromosome bands with potential candidate genes, for example, 11p11 [8] and 13q22.1 [9]. The role and function of these candidate regions are under investigation now.…”
Section: Introductionmentioning
confidence: 99%